The Influence Of Influencer Marketing And Content Marketing On Consumer Purchasing Decisions On Social Media (Tiktok Case Study) - Yanti Susanti; Mutia Haris; Aulia Kaila Rohmah (JMB : Jurnal Manajemen dan Bisnis, 2026)
The development of social media, particularly TikTok, has driven change in digital marketing strategies through the utilization of Influencer marketing and Content Marketing. This study aims to analyze the influencer of influencer Marketing and Content Marketing on consumers' purchasing decisions on TikTok social media. The research method used is a quantitative approach with a survey design. Data were collected through Likert-scale questionnaires distributed online to 50 TikTok users, with the sampling technique determined using the Slovin formula. Data analysis was conducted using IBM SPSS Statistics 25, including validity tests, reliability tests, T-tests, F-tests, and coefficient of determination analysis. The results indicate that Influencer Marketing and Content Marketing have a significant effect on purchasing decisions. The coefficient of determination shows that both independent variables are able to Influence purchasing decisions by 89,7%, while the remaining percentage is Influenced by other variables outside this study. These findings suggest that marketing strategies through Influencer Marketing and Content Marketing on TikTok play an important role in encouraging consumers' purchasing decisions on TikTok social media